Analysis Comparison of Plate and Beam Formwork Using Semi Conventional Formwork with Aluminium Formwork System in Terms of Cost and Duration on Vasanta Innopark Project - Deviana Cahyani; Anjas Handayani (Journal of World Conference (JWC), 2021)
The development of technology in the world of construction in Indonesia marked with the increasing number of innovations used in the construction process, one of which is formwork. Formwork is one of the most influential jobs on construction projects, especially in terms of cost and time. Therefore, modern Formwork innovations continue to emerge, one of which is Aluminium Formworks System. In this study the authors conducted comparative analysis of cost and time among semi-conventional Formwork with Aluminium Forcoand also spread questionnaires to find out if the Aluminium formworks are effective in replacing semi-conventional formworks on the Vasanta Innopark project. The results of the questionnaire will be analyzed using validity tests, realibility, correlation, and regression in SPSS software. The result of this research, the total cost needed for semi-conventional formwork is Rp. 6,577,699,867.20 and the total cost for the aluminium formwork is Rp. 6,985, 970.893.44 where aluminium formwork is more expensive by Rp 408,271,026.44 or 5.84% more expensive. And the time required conventional formwork is for 342 days while for aluminium formwork for 180 days or with a difference of 162 days or about 47.37 percent. And from the results of the questionnaire obtained that the effectiveness of aluminium formwork in replacing semi-conventional formwork is 0.833 or 83.3%.